Performance evaluation of 4.75-mm NMAS Superpave mixture - Rahman, Farhana (Kansas State University, 2010)
A Superpave asphalt mixture with 4.75-mm nominal maximum aggregate size (NMAS) is a promising, low-cost pavement preservation treatment for agencies such as the Kansas Department of Transportation (KDOT). The objective of this research study is to develop an optimized 4.75-mm NMAS Superpave mixture in Kansas. In addition, the study evaluated the residual tack coat application rate for the 4.75-mm NMAS mix overlay. Two, hot-in-place recycling (HIPR) projects in Kansas, on US-160 and K-25, were overlaid with a 15- to 19-mm thick layer of 4.75-mm NMAS Superpave mixture in 2007. The field tack coat application rate was measured during construction. Cores were collected from each test section for Hamburg wheel tracking device (HWTD) and laboratory bond tests performed after construction and after one year in service. Test results showed no significant effect of the tack coat application rate on the rutting performance of rehabilitated pavements. The number of wheel passes to rutting failure observed during the HWTD test was dependent on the aggregate source as well as on in-place density of the cores. Laboratory pull-off tests showed that most cores were fully bonded at the interface of the 4.75-mm NMAS overlay and the HIPR layer, regardless of the tack application rate. The failure mode during pull-off tests at the HMA interface was highly dependent on the aggregate source and mix design of the existing layer material. This study also confirmed that overlay construction with a high tack coat application rate may result in bond failure at the HMA interface. Twelve different 4.75-mm NMAS mix designs were developed using materials from the aforementioned but two binder grades and three different percentages of natural (river) sand. Laboratory performance tests were conducted to assess mixture performance. Results show that rutting and moisture damage potential in the laboratory depend on aggregate type irrespective of binder grade. Anti-stripping agent affects moisture sensitivity test results. Fatigue performance is significantly influenced by river sand content and binder grade. Finally, an optimized 4.75-mm NMAS mixture design was developed and verified based on statistical analysis of performance data.
Keywords: Superpave mixture; 4.75-mm NMAS; Tack coat; Dust-to-effective binder ratio; Performance prediction model; Optimization; Engineering, Civil (0543); Engineering, Materials Science (0794)